KUALITAS PELAYANAN PEMERINTAH DESA BOROBUDUR SETELAH ADANYA ALOKASI DANA DESA - Maryono Maryono (GEMA PUBLICA : Jurnal Manajemen dan Kebijakan Publik, 2019)
In Article 67 paragraph (2) of Law Number 6 Year 2014 concerning Villages, it is stated that the village has an obligation, among others, to improve the quality of life of the village community, develop village community empowerment, and provide and improve services to the village community. One program carried out by the government to realize this is the provision of Village FundsThe purpose of this paper is to find out how the quality of service in the village government of Borobudur after the allocation of village funds. This research is a type of survey research. This research was conducted on the residents of Borobudur Village. The population in this study was 9,030 with sampling determination techniques using the Slovin formula with an error rate of 10%, so the number of samples in this study were 100 respondents. Data collection techniques using questionnaires were then analyzed using index analysis. The results of the study prove that only the tangible aspect has the highest index value